Correlação entre indicadores socioeconômicos e demográficos e distribuição dos casos de COVID-19 nos estados brasileiros - Moraes, Adriani Izabel de Souza (Universidade Federal de São Carlos, 2023)
The Covid-19 pandemic hit the population in a heterogeneous way, especially in Brazil, which has a context of high social inequality. The objective of this study was to analyze the spatial correlation between socioeconomic and demographic indicators and the incidence of cases and deaths due to Covid-19 in Brazilian regions. This is an ecological study, carried out in Brazil from March 2020 to June 2022. Data regarding socioeconomic and demographic indicators were collected through the Continuous National Household Sample Survey, and data on cases and deaths of Covid-19 were obtained from the Ministry of Health website. For data analysis, the GeoDa 1.20.0.10 Software was used, calculating the Moran Global Indexes in a univariate and bivariate way, and QGIS 3.26.0 for preparing the maps. approval by the Ethics Committee for Research with Human Beings was required. During the study period, the state of Espírito Santo had the highest incidence of Covid-19 cases, 27,289.14/100,000 population, and Rio de Janeiro, the state with the highest number of deaths, 428.92/100,000 population. According to the analysis by Moran Global, hospitalization changed spatially positively in relation to mortality from Covid-19 in Brazil, that is, this variable is similar to the surrounding states, while the incidence of Covid-19 in the country was not identified. space.In addition, it was possible to identify spatially independent variables in relation to mortality from Covid-19, being moderately positive in relation to literate individuals, as well as white individuals and also individuals aged 20 to 59 years, that is, states with higher mortality also had the largest population with these profiles. Thus, it was concluded that there was a spatial transition between Covid-19 mortality and socioeconomic and demographic indicators in the states of Brazil; however, there was no spatial breathing between the incidence of Covid-19 and these variables.
Correlation between socioeconomic and demographic indicators and distribution of COVID-19 cases in Brazilian states
Keywords: Covid-19; Análise espacial; Indicadores sociais; Indicadores econômicos; Sars-Cov-2; Social indicators; Economic indicators; Spatial analysis; CIENCIAS DA SAUDE::ENFERMAGEM